(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article considers that an important place in the process of interaction between a student and a teacher is interpersonal communication. The image of a teacher is individual and depends not so much on the teacher, but on the characteristics of the student’s perception.